2016
DOI: 10.1111/pcmr.12442
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological induction of skin pigmentation unveils the neuroendocrine circuit regulated by light

Abstract: Light-regulated skin colour change is an important physiological process in invertebrates and lower vertebrates, and includes daily circadian variation and camouflage (i.e. background adaptation). The photoactivation of melanopsin-expressing retinal ganglion cells (mRGCs) in the eye initiates an uncharacterized neuroendocrine circuit that regulates melanin dispersion/aggregation through the secretion of alpha-melanocyte-stimulating hormone (α-MSH). We developed experimental models of normal or enucleated Xenop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 56 publications
2
35
1
Order By: Relevance
“…Implanted a-MSH-releasing minipumps in adult Xenopus laevis produced a long-lasting (12 days) increase in melanosome dispersion, and in the fish tilapia increased melanophore number (van Eys and Peters, 1981). In contrast, we found that GABA A R antagonists, which increase the synthesis and secretion of a-MSH from the embryonic Xenopus pars intermedia pituitary (Bertolesi et al, 2016), did not trigger a morphological skin pigmentation response (Figure 3B, C). To confirm that a-MSH does not influence embryonic morphological skin pigmentation, we treated embryos with repeated applications of fresh a-MSH, along with small incisions in the tail for a-MSH access to the tadpole, from stage 33 to stage 42 and assessed both physiological (positive control) and morphological skin pigmentation.…”
Section: Pharmacological Induction Of Physiological and Morphologicalmentioning
confidence: 72%
See 4 more Smart Citations
“…Implanted a-MSH-releasing minipumps in adult Xenopus laevis produced a long-lasting (12 days) increase in melanosome dispersion, and in the fish tilapia increased melanophore number (van Eys and Peters, 1981). In contrast, we found that GABA A R antagonists, which increase the synthesis and secretion of a-MSH from the embryonic Xenopus pars intermedia pituitary (Bertolesi et al, 2016), did not trigger a morphological skin pigmentation response (Figure 3B, C). To confirm that a-MSH does not influence embryonic morphological skin pigmentation, we treated embryos with repeated applications of fresh a-MSH, along with small incisions in the tail for a-MSH access to the tadpole, from stage 33 to stage 42 and assessed both physiological (positive control) and morphological skin pigmentation.…”
Section: Pharmacological Induction Of Physiological and Morphologicalmentioning
confidence: 72%
“…Ivermectin produced a significant increase in the number of melanophores around the eye ( Figure 3A-C), suggesting that ivermectin targets the morphological pigmentation pathway. Strychnine, however, did not induce morphological pigmentation ( Figure 3A-C), nor a physiological response (Bertolesi et al, 2016), arguing that GlyRs play no role in either pigmentation mechanism.…”
Section: Pharmacological Induction Of Physiological and Morphologicalmentioning
confidence: 90%
See 3 more Smart Citations